Infectious and parasitic disease of the nervous system : textbook for students-foreign citizen IV course of medical faculties of the speciality “Medicine” - Kozyolkin, O. A.; Vizir, I. V.; Sikorskay, M. V.; Козьолкін, Олександр Анатолійович; Візір, Ірина Володимирівна; Сікорська, Марина Володимирівна (Запорізький державний медичний університет, 2023)
The term “neuroinfection” does not refer to any single disease. This is a whole section of fairly common neurological pathologies (more than 42% of the total statistics). It included lesions of the nervous system caused by an infectious agent. In other words, neuroinfection is the general name for infectious diseases, the causative agent of which is localized in the nervous tissue and causes inflammation: the brain or its membranes; spinal cord; peripheral nerves. The etiological spectrum of neuroinfections is quite wide - viruses, bacteria, fungi, some types of protozoa. Of great importance are mixed infections, in which a symbiosis of pathogenic flora is detected. For example, herpetic neuroinfection - meningoencephalitis, encephalomyelitis. Taking into account the duration of the course of the disease, there may be neuroinfections that have a chronic (sluggish) character, or acute and subacute forms of lesions of the nervous system.